(untitled) (Citizenship in Action: Extension and Culture Magazine, 2025)
The objective was to verify changes in health dimensions in participants of a university extension program. This is a quantitative and cross-sectional study. Levels of physical activity (IPAQ), quality of life (WHOQoL), anxiety (BAI) and satisfaction with spiritual health (SWBQ) were evaluated. A comparison between the groups (frequent and dropouts) was performed with Shapiro Wilk and the paired T-test. There were 55% men, from the biological sciences (35%), without psychological follow- up and associated diseases (90%). With regard to physical activity, participants were considered very active, with average levels in all dimensions of quality of life and spiritual health, as well as mild scores for the level of anxiety. Thus, sports programs, in an extension format, can maintain or improve some health dimensions of the university population.